2014
DOI: 10.1017/s0022377814000956
|View full text |Cite
|
Sign up to set email alerts
|

Collisionless and collisional effects on plasma waves from a partition squeeze

Abstract: A simple 1D model is presented for the heating caused by cylindrically-symmetric plasma waves in a non-neutral plasma column due to the addition of a symmetric squeeze potential applied to the center of the column. We study this model by using analytical techniques and by using a numerical grids method solution, and we compare the results of this model to previous work (Ashourvan and Dubin (2014)). squeeze divides the plasma into passing and trapped particles; the latter cannot pass over the squeeze potential.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…For this case, we found that the end potentials satisfy d/ ¼ ÀdLðtÞ@/=@z; see the discussion preceding Eq. (21). Using this in Eqs.…”
Section: Appendix A: Numerical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this case, we found that the end potentials satisfy d/ ¼ ÀdLðtÞ@/=@z; see the discussion preceding Eq. (21). Using this in Eqs.…”
Section: Appendix A: Numerical Methodsmentioning
confidence: 99%
“…This has been done previously for a special case, as in Ref. 21. Here, we note that the largest collisional effect is the smoothing of the discontinuity in the energy of the bounce-averaged (adiabatic) distribution function, and so we consider only the bounce averaged portion of this equation, which dominates the plasma response in the regime of interest, ( x ( x b .…”
Section: Collisions and Heatingmentioning
confidence: 96%
See 1 more Smart Citation